Characterisation of mesothelioma-initiating cells and their susceptibility to anti-cancer agents - Pasdar, Elham Alizadeh; Smits, Michael; Stapelberg, Michael; Bajzikova, Martina; Stantic, Marina; Goodwin, Jacob; Yan, Bing; Stursa, Jan; Kovarova, Jaromira; Sachaphibulkij, Karishma; Bezawork-Geleta, Ayenachew; Sobol, Margaryta; et al. (PloS one, 2015)
Malignant mesothelioma (MM) is an aggressive type of tumour causing high mortality. One reason for this paradigm may be the existence of a subpopulation of tumour-initiating cells (TICs) that endow MM with drug resistance and recurrence. The objective of this study was to identify and characterise a TIC subpopulation in MM cells, using spheroid cultures, mesospheres, as a model of MM TICs. Mesospheres, typified by the stemness markers CD24, ABCG2 and OCT4, initiated tumours in immunodeficient mice more efficiently than adherent cells. CD24 knock-down cells lost the sphere-forming capacity and featured lower tumorigenicity. Upon serial transplantation, mesospheres were gradually more efficiently tumrigenic with increased level of stem cell markers. We also show that mesospheres feature mitochondrial and metabolic properties similar to those of normal and cancer stem cells. Finally, we show that mesothelioma-initiating cells are highly susceptible to mitochondrially targeted vitamin E succinate. This study documents that mesospheres can be used as a plausible model of mesothelioma-initiating cells and that they can be utilised in the search for efficient agents against MM.
Keywords: buněčné sféroidy; Mitochondria; Inhibitory Concentration 50; Mesothelioma, Malignant; nádory plic; Lung Neoplasms; myši nahé; Humans; tokoferoly; Disease Progression; Biomarkers, Tumor; Antineoplastic Agents; antigen CD24; Neoplasm Invasiveness; Phenotype; inhibiční koncentrace 50; Cell Adhesion; Mice, Nude; genový knockdown; lidé; mitochondrie; nádorové kmenové buňky; zvířata; proliferace buněk; Neoplastic Stem Cells; Gene Knockdown Techniques; Tocopherols; nádorové biomarkery; CD24 Antigen; Spheroids, Cellular; Neoplasm Transplantation; Mesothelioma; transplantace nádorů; mezoteliom; fenotyp; Cell Proliferation; nádorové buněčné linie; protinádorové látky; progrese nemoci; maligní mezoteliom; invazivní růst nádoru; Animals; buněčná adheze; Cell Line, Tumor